The Rivalry of Ahok Versus Anies in Jakarta Election 2017 - Mufrodi, Ali (Proceedings of International Conference on Muslim Society and Thought, 2017)
This article would like to discuss the rivalry between Basuki Tjahaja Purnama or Ahok the Governor incumbent, and Anies Baswedan, the Governor candidate, to challenge Ahok in Pilkada (District Election) DKI Jakarta 2017. How the campaign process held by them both to win the voters, the horizontal conflicts between the supporters of these two candidates. Jakarta Election 2017 not only bumping both groups. It also involving other groups such as nationalist groups which were  incorporated in politic parties like Koalisi Merah Putih (KMP = Gerindra, Demokrat, Partai Keadilan Sejahtera), the splinter group and theMuslim hard-line groups.